Critical & Emerging Perspectives in the Sociology of Mental Health 7 Illness - Magee, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
We begin by comparing psychological & psychiatric perspectives on mental health and illness with sociological perspectives. The emphasis is on how cultural and structural forces shape various professional and lay understandings of mental illnesses. We then switch our focus to institutions responsible for the control of mental illnesses. Mental health and illness over the life course is the broad heading under which most of my research falls, so I have included this as the third the topic of the course. I am also interested in applications and policy implications of sociological research , so one week is also dedicated to that topic. Topics to be converted in the last 5 weeks. There are typically few enough students in the course for everyone to have a week dedicated to a topic of their choice.